PROFIL GEJALA MENOPAUSE PADA PERAWAT DAN BIDAN DI RS DR. SAIFUL ANWAR MENGGUNAKAN MENOPAUSE RATING SCALE - Pande Made Dwijayasa; Nooryanto Muhammad; Teguh Wiyono; Ferdinand Umbu Pati (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
Menopause is a natural biological transition that typically occurs between 45 and 55 years of age and is often accompanied by somatic, psychological, and urogenital symptoms that may affect quality of life and work performance. Healthcare workers may be particularly vulnerable due to occupational stress and high physical and emotional demands. This descriptive cross-sectional study aimed to describe the profile of menopausal symptoms among nurses and midwives working in IRNA 3 at Dr. Saiful Anwar General Hospital, East Java, and was conducted from February to April 2025 using the Menopause Rating Scale (MRS). Of the 213 questionnaires collected, 121 eligible nurses and midwives aged 40–60 years were included after applying the inclusion and exclusion criteria. Data were collected using a demographic questionnaire and the validated Indonesian version of the MRS. Descriptive statistical analysis was performed. The mean age of participants was 46.94 ± 4.27 years. Most respondents were midwives (56.2%) and married (89.3%). Somatic and psychological symptoms were predominantly mild to moderate. The most frequently reported symptoms were joint and muscle pain, sleep disturbances, physical and mental exhaustion, and irritability. Hot flashes were commonly reported but less frequent than musculoskeletal and psychological complaints. Most participants reported no sexual problems, although moderate to severe vaginal dryness was relatively common. Menopausal symptoms among nurses and midwives were predominantly somatic and psychological in nature. Workplace monitoring and targeted support strategies are needed to maintain quality of life and professional performance during the menopausal transition. Keywords: healthcare workers, menopause, Menopause Rating Scale, midwives, nurses DOI 10.35990/mk.v9n2.p221-232